EFEKTIVITAS HYPNOTERAPI TEKNIK ANCHOR TERHADAP PERUBAHAN PERILAKU MEROKOK REMAJA Studi Pada Klien di Klinik Maulana Center of Hypnotherapy Palembang - Budiman Budiman (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2016)
Adolescent smoking behavior is one of the behaviors that are formed through the influence of the environment and the curiosity of a teenager on the enjoyment of cigarettes by a teenager. Smoking is also not only occurs in adolescent boys by the results of the study found that smoking behavior also applies to young women as well as children who are still in primary school. This study examines the effectiveness Anchor Techniques of Hypnoterapy toward Adolescent Smoking Behavior Change. Study for Client in The Clinic Maulana Center of Hypnotherapy Palembang. The hypothesis of this study is there Effect of Anchor Techniques of Hypnoterapy smoke Adolescent Behavior Change. Research for Clients in The Clinic Maulana Center of Hypnotherapy Palembang. This study included a quantitative study in which research methods used was Quasi Experiment design with pretest and posttest with non-control group design, a design study aimed at testing the causal relationship (Polit & Beck, 2006). This study will be conducted at the Clinic Maulana Center of Hypnotherapy Palembang on March-June 2015. The Clinic is located at street Kebun Bunga complex BNI Block B 4 Sukarami Palembang and sampling techniques using purposive sampling with 15 respondens and using t-test data analysis and MANOVA. The results of this study stated that there Effect Anchor Techniues of Hypnotherapy toward Adolescent Smoking Behavior Change. The changes meant is leading to better behavior and that, of 15 people treated with anchor techniques of hypnotherapy 11 people stop smoking while two people can reduce the intensity and frequency of smoking to 78% while the two others are only able to be able to reduce the intensity of smoking 56, 3%. It is advisable to adolescents to be more selective in choosing friends relations, peer groups, and the utilization of spare time with positive activities. Trying to avoid and try smoking, improve self-control and self-regulation to the development of technology and information in order to avoid negative environment.